Fractionated stereotactic radiation therapy for intact brain metastases - Samuel R. Marcrom, MD; Andrew M. McDonald, MD; Jonathan W. Thompson, MD; Richard A. Popple, PhD; Kristen O. Riley, MD; James M. Markert, MD; Christopher D. Willey, MD, PhD; Markus Bredel, MD, PhD; John B. Fiveash, MD (Advances in Radiation Oncology, 2017)
Purpose: Limited data exist on fractionated stereotactic radiation therapy (FSRT) for brain metastases. We sought to evaluate the safety and efficacy of FSRT and further define its role in brain metastasis management. Methods and materials: A total of 72 patients were treated with linear accelerator–based FSRT to 182 previously untreated, intact brain metastases. Targets received 25 or 30 Gy in 5 fractions. All targets within the same course received the same prescription regardless of size. Toxicity was recorded per Radiation Therapy Oncology Group central nervous system toxicity criteria. Results: The median follow-up was 5 months (range, 1-71 months). The Kaplan-Meier estimate of 12-month local control was 86%. Tumors <3 cm in diameter demonstrated improved 12-month local control of 95% compared with 61% in tumors ≥3 cm (P < .001). The Kaplan-Meier estimate of 12-month local control was 91% in tumors treated with 30 Gy and only 75% in tumors treated with 25 Gy (P = .015). Tumor diameter ≥3 cm resulted in increased local failure, and a 30 Gy prescription resulted in decreased local failure on multivariate analysis (hazard ratio [HR], 8.11 [range, 2.09-31.50; P = .003] and HR, 0.26 [range, 0.07-0.93; P = .038]). Grade 4 central nervous system toxicity occurred in 4 patients (6%) requiring surgery, and no patient experienced irreversible grade 3 or 5 toxicity. Increasing tumor diameter was associated with increased toxicity risk (HR, 2.45 [range, 1.04-5.742; P = .04]). Conclusions: FSRT for brain metastases appears to demonstrate a high rate of local control with minimal risk of severe toxicity. Local control appears to be associated with smaller tumor sizeand a higher prescription dose. FSRT is a viable option for those who are poor single-fraction candidates.